Establishment of Black Ant (Dolichoderus thoracicus)on Cocoa Plantation and Its Effects on Helopeltisspp. Infestation - Soekadar Wiryadiputra (Indonesian Coffee and Cocoa Research Institute, 2007)
Black ant (Dolichoderus thoracicus)is the efficient biological control agent in suppressing main cocoa pests. It was reported that besides controlling the cocoa mirids, Helopeltisspp., this agent also can be used for biological control of cocoa pod borer (Conopomorpha cramerella)and rodents pest. Nevertheles, establishment of black ant in cocoa plantation is difficult. The objectives of research were to obtain the best method of black ant establisment and to know its effect on suppressing population and infestation of Helopeltis spp. The experiment was conducted on two cocoa ecosystems, namely cocoa plantation with coconut shading trees and with Gliricidia sepium shading trees. There were six methods of black ant establisment tried using a combination between black ant nest types and innoculation of mealybug (Cataenococcus hispidus). A control plot also added on these trial, therefore seven treatments were tried in this experiment and each treatmentwasreplicated three times. The results revealedthat on cocoa shaded by coconuts, ant establishment by the nests of coconut leaves combined with mealybug(Cataenococcus hispidus)inoculation on husk wedges were the best method and could effectively control Helopeltis infestation. Good results of ant establishment also occurred on cocoa shaded by Gliricidia but its effect on Helopeltis infestation has not been significant. Four months after establishment of black ant on cocoa with coconut shading trees, Helopeltisspp. population on the plots treated by coconut leaves nest combined with innoculation of mealybug using husk wedges were very low, namely only one Helopeltisper 36 cocoa trees, whereas on control plot reaches of 85 Helopeltis. Infestation of Helopeltis measured by percentage of trees occupied by Helopeltisper 36 cocoa trees in the same period and treatment plot revealed also very low, namely 1.04% compared to 27.86% on that of the control plot. Key words : Cocoa, black ant (Dolichoderus thoracicus), coconut, Gliricidia sepium, mealybug(Cataenococcus hispidus), Helopeltis spp.